The Puppet Corridor and the Sahel Fault Line: Diverging Paths of Sovereignty in Contemporary Africa - Mohammed Sal (The Pan African Strategic Observatory, 2025)
This paper argues that recent events in the Sahel and Central Africa confirm, with a disturbing level of precision, a psychopolitical model of neo-colonial control first articulated in Pan-Africanism Reimagined and later formalised as Puppet Syndrome, the Imperial Selection Model (ISM), and the Puppet Diagnostic Index (PDI). While mainstream analysis still explains African instability in terms of “weak institutions,” “jihadist threats,” or “corruption,” we show that a more accurate predictor of outcomes is the psychological and relational profile of leadership and the corridors through which empire moves: mineral, diplomatic, military, and epistemic. We contrast two concurrent trajectories. In the Sahel, Mali, Burkina Faso, and Niger have expelled French troops, terminated key defence agreements, created the Alliance of Sahel States (AES), and formally withdrawn from ECOWAS, explicitly naming sovereignty and anti-imperial realignment as their horizon. In Central Africa, the Democratic Republic of Congo (DRC) under a high-TSFI (Trait–System Fit Index) leadership has moved in the opposite direction: accelerated IMF re-embedding, a tripled currency devaluation, and, most recently, a U.S.–DRC Strategic Partnership Agreement that reorganises critical mineral governance, infrastructure, and even domestic law in ways that structurally privilege foreign interests, including through the Lobito Corridor. We argue that (1) these developments validate earlier predictions about puppet leadership and imperial corridors with unusual precision, and (2) the Sahel’s current rupture represents exactly the “early awakening” zone that Pan-Africanism Reimagined anticipated would move before Central and Southern Africa. On this basis we propose a liberation blueprint organised around five axes: psychopolitical screening of leaders (PDI), re-engineering of regional blocs, sovereign economic and infrastructure design, de-colonial security doctrine, and epistemic reconstruction. Crucially, we specify clear falsification criteria and safeguards against pathologising individuals. Our claim is not that specific persons are inherently disordered, but that certain policy profiles and alliance patterns match trait-clusters (Dark Tetrad–like) that systematically correlate with neglect, legislative self-sabotage, and sovereignty erosion. If regimes that institutionalise indifference to their populations do not produce higher neglect-related excess mortality and structural dispossession, then our framework is wrong. We therefore present this work not as prophecy, but as a testable, uncomfortable, and urgently needed diagnostic tool.